2011
DOI: 10.1213/ane.0b013e31821f9544
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygenation Therapy Alleviates Chronic Constrictive Injury–Induced Neuropathic Pain and Reduces Tumor Necrosis Factor-Alpha Production

Abstract: These data show that HBOT alleviates CCI-induced neuropathic pain and inhibits endoneuronal TNF-α production, but not IL-1β in CCI-induced neuropathic pain. Reduced TNF-α production may, at least in part, contribute to the beneficial effect of HBOT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 46 publications
5
46
0
Order By: Relevance
“…Recent publications have reported variable outcomes in great part because of using protocols that differ significantly in depth, duration, frequency and number of sessions [36][37][38]. It appears that HBOT can be effective in decreasing chronic inflammation in the brain by reducing pro-inflammatory cytokine activation and through provocation of stem cell activity [7][8][9][10]. The repeat brain SPECT indicated the valuable contribution of this technique as a functional imaging biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications have reported variable outcomes in great part because of using protocols that differ significantly in depth, duration, frequency and number of sessions [36][37][38]. It appears that HBOT can be effective in decreasing chronic inflammation in the brain by reducing pro-inflammatory cytokine activation and through provocation of stem cell activity [7][8][9][10]. The repeat brain SPECT indicated the valuable contribution of this technique as a functional imaging biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…The treatments included 1) hyperbaric oxygen therapy (HBOT), 2) combination therapy of infused ketamine concurrent with transcranial magnetic stimulation (TMS), 3) injections of perispinal etanercept (PSE), and 4) non-invasive trans-nasal Sphenopalatine Ganglion (SPG) block. HBOT is believed to have anti-inflammatory effects, reducing the excess of proinflammatory cytokine activation such as TNF-alpha and facilitating improvement by provocation of stem cell activity [7][8][9][10]. The combination therapy of infused ketamine administered concurrent to TMS appears to address the abnormalities in brain circuits found both in treatment resistant depression and treatment resistant central pain [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches have reported that oxygen therapy appears to be effective in the pain management and show same effectiveness as hyperbaric oxygen. [14][15][16] Though studies have revealed the analgesic effect of hyperbaric oxygen in both rats and human with neuropathic pain, 13,[17][18][19] costs and poor availability limit the use of hyperbaric oxygen. These prompt us to investigate the effect of intermittent normobaric hyperoxia (InHO) in the treatment of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory cytokines such as tumor necrosis factor-alpha (TNF-α) which are released after nerve injury contribute to injury-induced peripheral nerve pathology and to the development of neuropathic pain [10][11][12][13]. TNF-α inhibitors may be administered subsequent to nerve injury where they have been shown to attenuate behavior indicative of neuropathic pain [14,15].…”
mentioning
confidence: 99%